2017
DOI: 10.1108/lr-02-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Organization and usage of information resources at Deeni Madaris libraries in Pakistan

Abstract: Purpose Deeni Madaris of Pakistan and their libraries are playing an important role in educating the large fraction of society. They have always been engaged in the development of social and cultural values of the Pakistani society. This study aims to investigate the organization of information resources and their utilization at Deeni Madaris libraries in the central Punjab, Pakistan. Design/methodology/approach Quantitative research approach was adopted for this study. A questionnaire was developed on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Digital literacy usually developed when librarians, teachers, and professors collaborated on the development of teaching standards. Besides, the educational institutions, more than 12,000 Deeni Madras "Religious institutions" running under the ministry of religious affairs government of Pakistan also required digital literacy training (Habib-ur-Rehman et al, 2017). The research revealed that these libraries are in a critical state in terms of information management using classification and cataloging standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital literacy usually developed when librarians, teachers, and professors collaborated on the development of teaching standards. Besides, the educational institutions, more than 12,000 Deeni Madras "Religious institutions" running under the ministry of religious affairs government of Pakistan also required digital literacy training (Habib-ur-Rehman et al, 2017). The research revealed that these libraries are in a critical state in terms of information management using classification and cataloging standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…42 • Lack of search and retrieval solution for multilingual resources written in Pashtu, Arabic, and Urdu. 43 • Limited or no use of big data analytics to improve acquisition, preservation, curation, and data analysis. 44 • Insufficient information on the websites regarding their libraries and lack of communication support for end users.…”
Section: Resource Description Discovery and Accessmentioning
confidence: 99%
“…Counterproductive behaviour is defined as such type of behaviour that disregards the norms of the rules of organization and its purpose is to harm the organization or people working their counterproductive behaviour can take different forms of violence, deviance, revenge, cyberloafing (Rehman, et al, 2017). Counterproductive behaviour is not only a single type of behaviour but also aggregated set of behaviours.…”
Section: Counterproductive Behaviourmentioning
confidence: 99%